Operational optimisation of a novel dual-piston linear compressor: Simulation and experiment. (December 2021) - Wei, Yidi; Zuo, Zhengxing; Jia, Boru; Liang, Kun; Feng, Huihua
Highlights: A novel dual piston linear compressor prototype is presented. The experimental results verify the established numerical model. Piston operation is a direct control variable, which means the volumetric efficiency can be regulated. The output characteristics, especially linear motor efficiency, depend heavily on the operating frequency and stroke. Abstract: A novel dual-piston linear compressor consisting of two piston-cylinder assemblies and a linear electric motor was constructed. To explore the performance of the dual-piston linear compressor, a numerical model that contains a thermodynamic sub-model, dynamic sub-model, three-phase linear motor sub-module, and control system sub-model was built. Several piston trajectories and different operating conditions were assessed to investigate the performance of the dual piston linear compressor. Results from both the simulation and experiments indicate that the system with the triangle curve trajectory exhibits the best performance. The output characteristics (mass flow rate, motor efficiency, mechanical efficiency, and overall efficiency) depend heavily on the operating frequency and the stroke of the piston. For the dual-piston linear compressor system that was designed, the overall efficiency can reach up to 57.59% when the system works at a frequency of 12 Hz and a stroke of 26 mm.